The use of nitrates as insecticides and its effect on health in foods produced by traditional farming method compared to foods produced by organic farming - al-Muallim, Maalim Hasan (مجلة العلوم الزراعية و البيئية و البيطرية : مجلة علمية محكمة ربع سنوية., 2022)
The study aimed to identify the quantity of nitrates present in food produced by the organic farming method compared to food produced by the traditional farming method. It also, aimed to identify the danger of the expansion the use of fertilizers and agricultural pesticides containing nitrates without proper supervision or awareness which leaves residues of nitrates in food, especially vegetables, and fruits that are eaten directly because of their harmful effect on human health and the extent of the risks that may be exposed to from eating foods containing nitrates among a sample from Prince Sattam bin Abdulaziz University employees. The number of the sample was (279) during Ragab, Sha'ban, and Ramadan in 1443 HD. Its average was 18.6% of the total sample. To achieve the study objectives, it relied on the descriptive and quantitative method for data collection where sample was identified that consumed food produced by traditional agriculture more than the same types of food produced by organic farming. The results of the laboratory analysis indicated that the nitrates ratio in the traditional food was with the average of 621.87 while the organically produced foods was with the average of 359, 05. The results of the survey indicated that (89.6%) of the total study sample had a bachelor's degree or higher, and (95.3%) were Saudi women. They also indicate that the study members' opinions about the meaning of organic products are that natural fertilizers are used in the cultivation of organic products, followed by the non-reliance on pesticides Then avoid using hormones as for the method of identifying organic products. It was found that 32% learned about organic products through television, and 22% through the market, while the motives for purchasing organic products were that they were of high quality by 23%, while 749 were healthy, while 10% believe that it is free of pollution. Individuals who get organic products through the supermarket were 55%, and that 13% from farms directly and individuals who prefer to buy traditional local products were 17%, while 57% prefer to buy local organic products, and that 4% prefer exported traditional products. The results indicate an increase in the consumption of organic products which may be due to avoiding harmful substances found in traditional products and obtaining healthy food that is safe from pollutants. Therefore, the researcher recommends conducting more research to identify the nutritional content of organic food products and compare them with traditional food products and knowing the health effects of both.